Nanomaterials for Application in Medicine and Biology - Giersig, Michael; Khomutov, Gennady B.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2008)
This volume contains research reports presented during the NATO Advanced Research Workshop (ARW) “Materials for Application in Medicine and Biology” held in Bonn, Germany, from October 4 to 6, 2006 at the center of advanced european studies and research (caesar). The application of nanomaterials in medicine and biology can be understood as the gathering and use of our current knowledge on nanoscale features of b- logical systems in order to learn how to design nanodevices for biomedical uses. The success of this approach, known as nano-engineering, will allow scientists to devise strategies for the design and construction of nanodevices to be used in clinical trials (diagnosis and therapeutic monitoring), as well as to develop products with potential applications in regenerative medicine. One goal of this conference was to bring together researchers from Eastern and Western countries, offering them a platform to meet and discuss results of their research work. Thus, the aim of this conference was not only to present the advancements in research achieved during the past years, but it had also been conceived as a concerted European effort where expertise, technologies, and ideas were broadly shared to accelerate this progress. The conference provided an interactive forum with more than 100 participants from 15 countries.
Biocompatible Nanomaterials and Nanodevices Promising for Biomedical Applications -- Isohelical DNA-Binding Oligomers: Antiviral Activity and Application for the Design of Nanostructured Devices -- DNA Self-Assembling Nanostructures Induced by Trivalent Ions and Polycations -- DNA-Based Synthesis and Assembly of Organized Iron Oxide Nanostructures -- DNA-Based Nanostructures: Changes of Mechanical Properties of DNA upon Ligand Binding -- Nanoconstructions Based on Spatially Ordered Nucleic Acid Molecules -- Nanospearing – Biomolecule Delivery and Its Biocompatibility -- Multifunctional Glyconanoparticles : Applications in Biology and Biomedicine -- Plasmonics of Gold Nanorods. Considerations for Biosensing -- Influence of the S-Au Bond Strength on the Magnetic Behavior of S-Capped Au Nanoparticles -- Long-Term Retention of Fluorescent Quantum Dots In Vivo -- Towards Polymer-Based Capsules with Drastically Reduced Controlled Permeability -- Polyelectrolyte-Mediated Transport of Doxorubicin Through the Bilayer Lipid Membrane -- Network Model of Acetobacter Xylinum Cellulose Intercalated by Drug Nanoparticles -- Theoretical Approaches to Nanoparticles.
Keywords: Nanotechnology; Medicine; Biomaterials; Physical chemistry; Neurosciences; Nanotechnology; Biomedicine, general; Biomaterials; Physical Chemistry; Neurosciences